Changes in the trade pattern in China under the RCEP: an analysis of trade creation and diversion using the SMART-WITS model - Zhang, Wenjie; Abd Rahman, Muhammad Daaniyall; Muhamad Senan, Mohamad Khair Afham (Canadian Center of Science and Education, 2024)
The Regional Comprehensive Economic Partnership (RCEP), one of the globe's most expansive free trade agreements (FTAs), has profoundly influenced its member countries' trading patterns. This fact is especially critical for a major economic powerhouse such as China. Understanding its trade creation and trade diversion within the RCEP context can facilitate successful formulation strategies and result in effective economic policies. In this study, we utilize the World Integrated Trade Solution Software for Market Analysis and Restrictions on Trade (WITS-SMART), a partial equilibrium modeling tool, on both state-level and industrial-tier tariff reductions under two distinct scenarios. Our findings confirm that China will benefit from impactful trade results across all RCEP members. Looking from industry point of view: machinery, chemicals, metals sector together with plastics and rubber production are projected to enjoy maximum rewards through increased trade creation and diversion opportunities from Japan and Korea. On the contrary, Australia and ASEAN have the greatest influence on the animal and vegetable sector. This crucial understanding creates strategic indicators that aid in evaluating the most appropriate alignments to harness the untapped potential in the RECP domain.